Análise dos relatórios de sustentabilidade do varejo supermercadista brasileiro de grande porte - Resina, Rodrigo Alexandre (2013)
The quest for sustainable development is becoming more widespread among government, private organizations and members of civil society, motivated primarily by environmental imbalance and social problems. So the companies conceptualize measure and work toward sustainability and it has become the goal of many of these organizations. This research aimed to analyze how large retail supermarkets companies, that have operation in Brazil, measure their practices aimed at sustainable development. It was carried out during the research, a review of theory and the multiple case studies exploratory; it realized the data collection through public documents (Sustainability reports). First, it’s analyzed 32 reports of 3 retail businesses for several years. It was analyzed as indicators of sustainability are reported by companies in the sector, it was also assessed developments in the application of sustainability reporting in retail and sustainability dimension is prioritized in the reporting of organizational management. It observed a non- regular reporting on sustainability in the periods analyzed, companies report a higher number of indicators related social issues and despite the use of the GRI indicators, the companies had different interpretations about the same indicators. Thus, it identified that companies need to improve their reports and using the external validation (audit) to ensure the transparency and quality of sustainable reporting, enabling the retail supermarket companies to act towards a sustainable management.